2018
DOI: 10.1186/s12919-018-0124-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the performance of gene-based tests of genetic association when testing for association between methylation and change in triglyceride levels at GAW20

Abstract: Although methylation data continues to rise in popularity, much is still unknown about how to best analyze methylation data in genome-wide analysis contexts. Given continuing interest in gene-based tests for next-generation sequencing data, we evaluated the performance of novel gene-based test statistics on simulated data from GAW20. Our analysis suggests that most of the gene-based tests are detecting real signals and maintaining the Type I error rate. The minimum p value and threshold-based tests performed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In contrast, candidate gene-based association studies use genetic variation in genes known or suspected to play a functional role in a phenotypic trait of interest [ 15 , 17 , 22 ]. This approach has appealing features, including reducing the substantial multiple testing penalties required for GWAS and directly connecting statistical testing with functional biological units [ 23 , 24 ]. Several studies have successfully identified associations between SNPs in candidate genes and phenotypic traits in plants such as sugarcane [ 25 ], rubber tree [ 26 ], wheat [ 27 ], and ryegrass [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, candidate gene-based association studies use genetic variation in genes known or suspected to play a functional role in a phenotypic trait of interest [ 15 , 17 , 22 ]. This approach has appealing features, including reducing the substantial multiple testing penalties required for GWAS and directly connecting statistical testing with functional biological units [ 23 , 24 ]. Several studies have successfully identified associations between SNPs in candidate genes and phenotypic traits in plants such as sugarcane [ 25 ], rubber tree [ 26 ], wheat [ 27 ], and ryegrass [ 28 ].…”
Section: Introductionmentioning
confidence: 99%